2016
DOI: 10.1103/physrevb.94.115128
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing Majorana zero-energy modes in a periodically gated quantum wire

Abstract: We explore a scheme for engineering a one-dimensional spinless p-wave superconductor hosting unpaired Majorana zero-energy modes, using an all-electric setup with a spin-orbit coupled quantum wire in proximity to an s-wave superconductor. The required crossing of the Fermi level by a single spin-split energy band is ensured by employing a periodically modulated Rashba interaction, which, assisted by electron-electron interactions and a uniform Dresselhaus interaction, opens a gap at two of the spin-orbit shift… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 117 publications
0
10
0
Order By: Relevance
“…In this case 36 , the topological phase diagram becomes more complex than for the uniformly covered nanowire (due to the presence of longitudinal minibands created by the periodicity of the system), and extends over a wider region in parameter space (to lower Zeeman fields and higher values of the chemical potential). Levine et al 36 considered a minimal 1D model for the nanowire superstructure, in a similar fashion to other previous studies [37][38][39][40] with related periodic structures. However, in the last couple of years it has been shown that the electrostatic environment and the three-dimensionality of these wires play an important role in all aspects concern-ing the trivial/topological phases and the appearance of MBSs.…”
Section: Introductionmentioning
confidence: 86%
“…In this case 36 , the topological phase diagram becomes more complex than for the uniformly covered nanowire (due to the presence of longitudinal minibands created by the periodicity of the system), and extends over a wider region in parameter space (to lower Zeeman fields and higher values of the chemical potential). Levine et al 36 considered a minimal 1D model for the nanowire superstructure, in a similar fashion to other previous studies [37][38][39][40] with related periodic structures. However, in the last couple of years it has been shown that the electrostatic environment and the three-dimensionality of these wires play an important role in all aspects concern-ing the trivial/topological phases and the appearance of MBSs.…”
Section: Introductionmentioning
confidence: 86%
“…with the phase ϕ kept as a free parameter. Here, µ 1 (x) is a periodic potential that can emerge due to external gates [68] or via a coupling to the phonons [69]. The parameter B parametrizes the strength of the term, while the phase ϕ, which is clearly an irrelevant parameter when periodic boundary conditions are imposed, becomes essential in the case of open boundary conditions.…”
Section: Hamiltonianmentioning
confidence: 99%
“…The parameter B parametrizes the strength of the term, while the phase ϕ, which is clearly an irrelevant parameter when periodic boundary conditions are imposed, becomes essential in the case of open boundary conditions. The manipulation of the phase ϕ can be envisioned if µ 1 (x) is due to external finger gates [68]. In this case, the spatial variations of the potential can be fully manipulated.…”
Section: Hamiltonianmentioning
confidence: 99%
“…In condensed matter physics, the Majorana ZM emerging in topological superconductors [4,5] has attracted much attention, because it not only gives fundamental and valuable information of quantum properties originating from non-abelian statistics [6], but also has a capability to carry out topologically protected quantum computing [7,8] and Majorana qubits [9][10][11][12][13][14]. For these purposes, realization and control of the Majorana ZMs are urgent issues in current technologies of nano fabrication from both theoretical and experimental points of view [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], and moreover these studies bring numerous discussions on the effects of dimerization, quasiperiodicity, disorder and interaction .…”
Section: Introductionmentioning
confidence: 99%